2011
DOI: 10.3109/15563650.2011.597034
|View full text |Cite
|
Sign up to set email alerts
|

Acute plant poisoning: Analysis of clinical features and circumstances of exposure

Abstract: INTRODUCTION: Human contact with potentially toxic plants, which may occur through abuse or by accident or attempted suicide, is frequent and sometimes results in clinically significant toxicity. OBJECTIVE: The aim of the present study was to identify which plants may lead to severe poisoning, and to define the clinical relevance of plant toxicity for humans in Switzerland. METHODS: We analyzed 42,193 cases of human plant exposure and 255 acute moderate, severe, and lethal poisonings, which were reported to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 32 publications
2
38
0
2
Order By: Relevance
“…Mahonia 279 Table 2 small differences, to the rank order seen in other studies conducted in Germany [2] and Switzerland [3][4][5]. While the rate of accidental exposures to plant genera like Taxus, Ligustrum, and Ficus was continuously high during the whole study period, the exposure by abuse to plant genera like Brugmansia and Datura showed time-dependent changes with the highest rate being in 2001 and a decreasing frequency in the following years.…”
Section: Zamioculcas 24mentioning
confidence: 73%
See 1 more Smart Citation
“…Mahonia 279 Table 2 small differences, to the rank order seen in other studies conducted in Germany [2] and Switzerland [3][4][5]. While the rate of accidental exposures to plant genera like Taxus, Ligustrum, and Ficus was continuously high during the whole study period, the exposure by abuse to plant genera like Brugmansia and Datura showed time-dependent changes with the highest rate being in 2001 and a decreasing frequency in the following years.…”
Section: Zamioculcas 24mentioning
confidence: 73%
“…
Plant exposures are described to be one of the most frequent reasons for calls to poison information centres in Germany [1,2] and Switzerland [3][4][5]. In a recent study in the United States 0%); adults 11.3 % (middle-aged adults 5.2%).
…”
mentioning
confidence: 99%
“…Alkaloids present in the plant: atropine, scopolamine, hyoscyamine (Fuchs et al, 2011), have strong anticholinergic properties (Soler-Rodríguez et al, 2006). But the plant also contains: daturine, and may contain a large amount of nitrates (Mezzasalma et al, 2016).…”
Section: Poisoning With Plants Containing Alkaloidsmentioning
confidence: 99%
“…However, they are less likely adverse effects than in using conventional drugs and if such effects occur, they are mild and only affecting a small number of people (Philomena, 2011;Spiteri Staines, 2011). Contact with plants was rarely responsible for serious poisoning (Fuchs et al, 2011). Flowering plants produce thousands of secondary metabolites (alkaloids, flavonoids, saponins, tanins, essential oils, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Leaves of wild plants collected during spring for food purpose may be responsible for intoxications. Its raw leaves are mainly used to flavour spreads based on cottage cheese, soups and sauces (Gilotta and Brvar, 2010;Fuchs et al, 2011). Dried leaves usually have a very faint odour (Colombo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%